2010
DOI: 10.2166/wst.2010.925
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial activity on polar xenobiotic degradation in activated sludge systems

Abstract: The influence of activated sludge quality on the co-metabolic biodegradation of three aminocarboxylic [corrected] acids was investigated for a variety of Luxembourg sewage treatment plants. A combination of biodegradation experiments and respirometric techniques are presented as a reliable approach for the estimation of biokinetics and biological xenobiotic degradation rates that allow for identification of governing parameters such as microbial activity and active biomass. Results showed that biokinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In contrast, aerobic heterotrophs can use a wide variety of organic substrates, sometimes very complex and with different physicochemical properties, which leads to a huge number of candidate enzymes that could contribute to OMPs biotransformation (Achermann et al, 2020;Fischer and Majewsky, 2014;Gulde et al, 2016;Krah et al, 2016). This complexity has resulted in very few studies trying to determine the key enzymes involved in the heterotrophic breakdown of OMPs, despite acknowledging that the heterotrophic biomass governs or enhances the cometabolic removal of many compounds, such as aminopolycarboxylic acids, sulfamethoxazole, diclofenac, paracetamol and 17-α-ethinylestradiol (Kennes-Veiga et al, 2020;Larcher and Yargeau, 2013;Majewsky et al, 2011Majewsky et al, , 2010Tran et al, 2009). Furthermore, it has been reported that heterotrophs and autotrophs can cooperate to remove OMPs and attenuate the presence of intermediate transformation products (TPs).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, aerobic heterotrophs can use a wide variety of organic substrates, sometimes very complex and with different physicochemical properties, which leads to a huge number of candidate enzymes that could contribute to OMPs biotransformation (Achermann et al, 2020;Fischer and Majewsky, 2014;Gulde et al, 2016;Krah et al, 2016). This complexity has resulted in very few studies trying to determine the key enzymes involved in the heterotrophic breakdown of OMPs, despite acknowledging that the heterotrophic biomass governs or enhances the cometabolic removal of many compounds, such as aminopolycarboxylic acids, sulfamethoxazole, diclofenac, paracetamol and 17-α-ethinylestradiol (Kennes-Veiga et al, 2020;Larcher and Yargeau, 2013;Majewsky et al, 2011Majewsky et al, , 2010Tran et al, 2009). Furthermore, it has been reported that heterotrophs and autotrophs can cooperate to remove OMPs and attenuate the presence of intermediate transformation products (TPs).…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of biological wastewater treatment have been discussed as relevant for micropollutant removal, including solid retention time (SRT) ( Clara et al., 2005 , Maeng et al., 2013 , Petrie et al., 2014 ), hydraulic retention time (HRT) ( Gros et al., 2010 ), nitrification ( Tran et al., 2009 , Helbling et al., 2012 , Sathyamoorthy et al., 2013 ), heterotrophic activity ( Majewsky et al., 2010 ), redox conditions ( Suarez et al., 2010 , Xue et al., 2010 ), pH ( Gulde et al., 2014 ) and suspended/attached growth ( Zupanc et al., 2013 , Falås and Longrée, 2013 ). A general consensus on the main drivers for the biological micropollutant removal at WWTPs is, however, lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of these GCs compounds in wastewater treatment plants (WWTPs) has been extensively studied and the scientists has considered biological treatment technology as critical to micropollutant removal [78]. Biological wastewater treatments have to consider some factors regarding micropollutant removal, such as solid retention time (SRT) [79,80] pH, hydraulic retention time (HRT) [81], nitrification [82,83] redox conditions [84,85], suspended/attached growth [86], and heterotrophic activity [87]. Although the main driving factor for the permanently biological micropollutant removal at WWTPs is still unknown [88].…”
Section: Properties Of Frequently Found Glucocorticoids In Watermentioning
confidence: 99%